1999
DOI: 10.1002/(sici)1097-010x(19990601)283:7<725::aid-jez10>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Organic osmolyte channels in cell volume regulation in vertebrates

Abstract: Volume‐activated organic osmolyte channels are found in a variety of vertebrates and cell types and show both common and disparate features. Upon exposure to hypotonic conditions, organic compounds such as taurine are released through these channels, reducing the intracellular solute concentration and thereby restoring cell volume. Various structurally diverse membrane proteins have been proposed as the channel. Accumulating evidence suggests that some of these proteins may play a more significant role as regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…We report a release pathway for organic osmolytes in intestine 407 epithelial cells, distinct from the compensatory anion efflux reported previously (53,55,57) and regulated by PKC. Hyposmotic release of organic osmolytes such as taurine, betaine, and inositol has been observed in many different cell models (2,3,12,17,25,45,46). Unlike chloride ions, which can have additional effects on enzyme activity, membrane potential, and, in muscle and nerve cells, the generation of action potentials, these organic osmolytes do not affect other cellular functions, making them especially suitable for volume regulation (2,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We report a release pathway for organic osmolytes in intestine 407 epithelial cells, distinct from the compensatory anion efflux reported previously (53,55,57) and regulated by PKC. Hyposmotic release of organic osmolytes such as taurine, betaine, and inositol has been observed in many different cell models (2,3,12,17,25,45,46). Unlike chloride ions, which can have additional effects on enzyme activity, membrane potential, and, in muscle and nerve cells, the generation of action potentials, these organic osmolytes do not affect other cellular functions, making them especially suitable for volume regulation (2,13).…”
Section: Discussionmentioning
confidence: 99%
“…In a number of cell types, the efflux of organic osmolytes and anion conductance was regulated similarly, suggesting that a single release pathway is involved [i.e., volume-sensitive organic osmolyte and anion channel (VSOAC)] (16, 22-24, 40, 47). In other cells, however, distinct pathways and/or transporters have been proposed (40,46). Indeed, in hippocampal slice preparations, at least two pathways for taurine release have been identified that differ in their kinetics of activation/inactivation and in their sensitivity for inhibitors (11).…”
mentioning
confidence: 99%
“…The contribution of organic osmolyte efflux to RVD in eukaryotic cells is variable, playing a significant role in protozoa and other invertebrates but being considerably less important in lower vertebrates and some mammalian cells [111,195,216,242,253,268]. The great majority of mammalian cells, however, respond to rapid volume increases by the activation of transport pathways (exchangers and/or cotransporters and/or channels) mainly for K + and Cl -but also for Na + , H + and HCO 3 -, together with the release of numerous small organic osmolytes like sugars, polyols, methylamines, amino acids or urea [225]. The relative contribution of organic anions to RVD is difficult to quantify and has, in many instances, been estimated by assuming that the cation efflux is balanced by anionic organic osmolytes [124,146,256].…”
Section: Mechanisms For Rvd In Mammalian Cellsmentioning
confidence: 99%
“…In many vertebrate cells the release of organic osmolytes during RVD is facilitated by a swelling-activated channel, which in most, but not all, cases [225] is preferentially anion selective [139,281]. In other vertebrate cells however, the osmolyte and ion pathways appear to be distinct from each other [191,269,277,285] but are still mediated by a channel rather than a transporter [139,147].…”
Section: Mechanisms For Rvd In Mammalian Cellsmentioning
confidence: 99%
“…Cells which undergo volume expansion when placed in hypotonic media control their volume through a process known as regulatory volume decrease (RVD), in which ions and organic osmolytes leave the cells, followed by water [2,15]. Organic osmolytes exit cells through channels which, in many cases, are thought to be swellingactivated anion channels [14].…”
Section: Introductionmentioning
confidence: 99%